Thermoplastic resin composition and electromagnetic wave-shielding material composed of the thermoplastic resin composition

By adding electromagnetic wave shielding materials such as carbon nanotubes and carbon black to the thermoplastic polyester elastic resin, the formulation and processing technology of the composition are optimized, and the problem of insufficient electromagnetic wave absorption and shielding performance in the prior art is solved, and an efficient, lightweight and temperature-stable electromagnetic wave shielding effect is achieved.

JP2025060120APending Publication Date: 2025-04-10TORAY CELANESE CO LTD +2

Patent Information

Application Number
JP2023170650
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

The prior art has challenges in suppressing the failure of millimeter-wave radar and improving the absorption efficiency of electromagnetic waves. In particular, the high density and low absorption efficiency of metal oxides lead to an increase in material usage, and the material's fluidity and temperature stability are insufficient when electromagnetic wave shielding is performed in the ECU unit of ADAS.

Method used

A thermoplastic polyester elastic resin composition is used, which contains 80.0% to 99.5% of the thermoplastic polyester elastic resin (A) and 0.5% to 20.0% of the first and second electromagnetic wave shielding materials (B and C), wherein the first electromagnetic wave shielding material is carbon nanotube and the second electromagnetic wave shielding material is carbon black. By optimizing the formulation and processing technology of the composition, its electromagnetic wave absorption and shielding properties are improved.

Benefits of technology

It achieves efficient electromagnetic wave absorption and shielding performance, improves the fluidity and temperature stability of the material, reduces weight, and maintains good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060120000001
    Figure 2025060120000001
  • Figure 2025060120000002
    Figure 2025060120000002
  • Figure 2025060120000003
    Figure 2025060120000003
Patent Text Reader

Abstract

To provide a thermoplastic resin composition which has a high absorption rate of electromagnetic waves around millimeter waves, and an electromagnetic wave-shielding material composed of the thermoplastic resin composition.SOLUTION: A thermoplastic polyester elastomer resin composition is composed of 80.0 to 99.5 mass% of a thermoplastic polyester elastomer resin (A) and 0.5 to 20.0 mass% of the total of a first electromagnetic wave-shielding substance (B) and a second electromagnetic wave-shielding substance (C), wherein the first electromagnetic wave-shielding substance (B) is contained in the thermoplastic polyester elastomer resin (A) so that a reflection attenuation rate of the electromagnetic waves is 60% or more, the second electromagnetic wave-shielding substance (C) is contained in the thermoplastic polyester elastomer resin (A) so that a transmission attenuation rate of the electromagnetic wave is 80% or more, and the thermoplastic polyester elastomer resin (A) is a polyester block copolymer containing 80 to 10 mass% of a high melting point crystalline polymer segment (a1) mainly composed of a crystalline aromatic polyester unit, and 10 to 80 mass% of a low melting point polymer segment (a2) mainly composed of an aliphatic polyether unit and / or an aliphatic polyester unit, as main components.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition and an electromagnetic wave shielding material comprising the thermoplastic resin composition. [Background technology]

[0002] Millimeter-wave radar, which uses electromagnetic waves in the frequency band of 30 GHz to 300 GHz, classified as millimeter waves among electromagnetic waves, is currently being used in various fields such as autonomous driving systems for automobiles, drones, industrial machinery, and medical and nursing devices, in addition to being applied to "5G communication technology" used in communication with smartphones, etc. In particular, millimeter-wave vehicle-to-vehicle radars (LRR) and millimeter-wave proximity radars (SRR) using millimeter waves of 76 GHz to 80 GHz are installed and operated as key technologies for advanced driver assistance systems (ADAS). In these applications, in order to ensure the operational accuracy of radar sensing, it is necessary to absorb unnecessary leakage and reflection of electromagnetic waves that cause noise. The energy of such electromagnetic waves can be absorbed by converting it into heat, and materials for absorbing electromagnetic waves can be classified into magnetic loss types composed of magnetic materials such as metal oxides, and dielectric loss types composed of dielectric materials such as conductive materials.

[0003] For example, as an example of a magnetic loss type electromagnetic wave absorbing material, Patent Document 1 discloses that an electromagnetic wave absorbing sheet made by forming a specific magnetic iron oxide into a sheet with a resin binder can be used to absorb electromagnetic waves in the frequency band from tens of GHz to hundreds of GHz.

[0004] On the other hand, dielectric loss type electromagnetic wave absorbers can be made to absorb electromagnetic waves by forming them into a three-dimensional shape that is tapered in the direction of incidence of the radio waves, such as a pyramid or wedge shape, or by dispersing a material with a high dielectric constant in a flat material, such as a sheet, to absorb electromagnetic waves.

[0005] As an example of an electromagnetic wave absorbing material configured in a planar shape, there is known a material in which the above-mentioned metal oxide or a carbon material, which is a dielectric, is dispersed in an organic material and processed into a shape such as a case or a sheet. As an example of such a material, Patent Document 2 discloses a pressed film in which a sintered body is prepared by interposing silver fine particles between a carbon material, which is a dielectric loss material, and the sintered body is used as an electromagnetic wave absorber. Patent Document 3 discloses a thermoplastic resin composition for an electromagnetic wave absorber, which is a thermoplastic resin composition containing a thermoplastic resin and a specific carbon nanotube, and is characterized in that the maximum height Sz of the sheet surface of a sheet having a thickness of 100 μm formed from the thermoplastic resin composition is 5 μm or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2023-067902 A [Patent Document 2] Patent No. 6905834 specification [Patent Document 3] Patent No. 6927448 specification Summary of the Invention [Problem to be solved by the invention]

[0007] An important issue with the above-mentioned millimeter wave radar is how to prevent malfunctions, and there is a demand for electromagnetic wave absorbers with a high electromagnetic wave absorption rate that can prevent the transmission of millimeter waves, which is the cause of malfunctions. In addition, the metal oxides used in conventional technology have a large specific gravity, and when used to counter millimeter wave interference, they have poor absorption efficiency, so a large amount of electromagnetic wave absorbing material must be used, which not only increases the specific gravity but also causes problems with poor moldability.For electromagnetic wave shielding applications in ECU units in ADAS, it is important that the material not only has excellent moldability, but also has stable material properties from cold to high temperatures, as well as being lightweight. In order to solve these problems, the present invention aims to provide a thermoplastic resin composition that is excellent in toughness, impact resistance and moldability, and also has a high absorption rate of electromagnetic waves, mainly millimeter waves, and an electromagnetic wave shielding material made of the thermoplastic resin composition. [Means for solving the problem]

[0008] The present invention provides the following electromagnetic wave shielding material having a high absorption rate of millimeter waves. That is, the thermoplastic resin composition of the present invention and the electromagnetic shielding material comprising the thermoplastic resin composition comprise the following first to tenth aspects of the present invention.

[0009] A first invention is a thermoplastic polyester elastomer resin composition comprising 80.0-99.5 mass% of a thermoplastic polyester elastomer resin (A) and 0.5-20.0 mass% in total of a first electromagnetic wave shielding material (B) and a second electromagnetic wave shielding material (C), in which the first electromagnetic wave shielding material (B) is contained in the thermoplastic polyester elastomer resin in an amount that causes an electromagnetic wave reflection attenuation rate of 60% or more, and the second electromagnetic wave shielding material (C) is contained in the thermoplastic polyester elastomer resin in an amount that causes an electromagnetic wave transmission attenuation rate of 80% or more, and the thermoplastic polyester elastomer resin (A) is a polyester block copolymer mainly composed of 80-10 mass% of a high melting point crystalline polymer segment (a1) mainly composed of crystalline aromatic polyester units and 10-80 mass% of a low melting point polymer segment (a2) mainly composed of an aliphatic polyether unit and / or an aliphatic polyester unit.

[0010] The second invention is a thermoplastic polyester elastomer resin composition according to the first invention, wherein when a 2 mm-thick plate obtained by molding the thermoplastic polyester elastomer resin composition is irradiated with electromagnetic waves having a frequency of 76 GHz to 80 GHz, the electromagnetic wave absorption rate measured by a free space method is 60% to 90%.

[0011] A third invention is a thermoplastic polyester elastomer resin composition according to the first invention, which has a temperature of 20°C or lower showing a maximum value of a loss factor measured by a tensile vibration non-resonance method in accordance with JIS K7244.

[0012] A fourth invention is a thermoplastic polyester elastomer resin composition according to the first invention, wherein a test piece molded in accordance with JIS K7161 has a tensile elongation at break of 200% or more.

[0013] A fifth invention is a thermoplastic elastomer resin composition according to the first invention, which has a notched Izod impact strength of 200 J / m notch or more measured at a temperature of 23°C and a notched Izod impact strength of 100 J / m notch or more measured at a temperature of -20°C, according to JIS K7110.

[0014] A sixth aspect of the present invention is a thermoplastic polyester elastomer resin composition according to the first aspect of the present invention, wherein the first electromagnetic wave shielding material (B) is carbon nanotubes and the second electromagnetic wave shielding material (C) is carbon black.

[0015] The seventh invention is the first invention, wherein the surface resistivity of a molded product obtained by molding the thermoplastic polyester elastomer resin composition is 1.0×10 6 (Ω / sq.) or more 1.0×10 16 (Ω / sq.) or less.

[0016] An eighth invention is a thermoplastic polyester elastomer resin composition according to the first invention, which further comprises a dispersant (D) for dispersing the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) in the thermoplastic polyester elastomer resin.

[0017] A ninth invention is a thermoplastic polyester elastomer resin composition according to the eighth invention, wherein the dispersant is any one of paraffin wax, montan wax, amide wax, ethylene bisstearic acid amide, fatty acid metal salt, silicone, polyolefin wax, or any combination thereof.

[0018] A tenth aspect of the present invention is an electromagnetic wave shielding material obtained by molding the thermoplastic polyester elastomer resin composition according to any one of the first to ninth aspects of the present invention. Effect of the Invention

[0019] According to the present invention, it is possible to provide a thermoplastic resin composition which is excellent in moldability, lightweight and has excellent electromagnetic wave absorbing properties, and an electromagnetic wave shielding material made of the thermoplastic resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, embodiments for carrying out the present invention will be described in detail.

[0021] [Thermoplastic polyester elastomer resin composition] The thermoplastic polyester elastomer resin composition for carrying out the present invention is a thermoplastic polyester elastomer resin composition comprising 80.0% by mass or more and 99.5% by mass or less of a thermoplastic polyester elastomer resin (A) and 0.5% by mass or more and 20.0% by mass or less of a first electromagnetic wave shielding material (B) and a second electromagnetic wave shielding material (C), in which the first electromagnetic wave shielding material (B) is in an amount that provides an electromagnetic wave reflection attenuation rate of 60% or more, and the second electromagnetic wave shielding material (C) is in an amount that provides an electromagnetic wave transmission attenuation rate of 80% or more, The thermoplastic polyester elastomer resin composition is characterized in that each of the thermoplastic polyester elastomer resins (A) is contained in the thermoplastic polyester elastomer resin (A), and the thermoplastic polyester elastomer resin (A) is a polyester block copolymer mainly composed of 80 to 10 mass % of a high melting point crystalline polymer segment (a1) mainly composed of a crystalline aromatic polyester elastomer and 10 to 80 mass % of a low melting point polymer segment (a2) mainly composed of an aliphatic polyether unit and / or an aliphatic polyester unit.

[0022] [Thermoplastic polyester elastomer resin (A)] The thermoplastic polyester elastomer resin (A) of the present invention comprises, as its constituent components, hard segments consisting of crystalline aromatic polyester units and soft segments consisting of aliphatic polyether units and / or aliphatic polyester units.

[0023] The hard segment is a polyester formed from an aromatic dicarboxylic acid or its ester bond-forming derivative (hereinafter, sometimes referred to as an "acid component") and a diol or its ester bond-forming derivative (hereinafter, sometimes referred to as a "diol component"). Specific examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, anthracene dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, diphenoxyethane dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 5-sulfoisophthalic acid, and sodium 3-sulfoisophthalate.

[0024] In the present invention, the aromatic dicarboxylic acid is mainly used, but a part of the aromatic dicarboxylic acid may be replaced with an alicyclic dicarboxylic acid such as 1,4-cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, 4,4'-dicyclohexyldicarboxylic acid, etc., or an aliphatic dicarboxylic acid such as adipic acid, succinic acid, oxalic acid, sebacic acid, dodecanedioic acid, dimer acid, etc. Furthermore, ester-forming derivatives of dicarboxylic acids, such as lower alkyl esters, aryl esters, carbonate esters, and acid halides, can also be used.

[0025] Next, specific examples of the diol include diols having a molecular weight of 400 or less, for example, aliphatic diols such as 1,4-butanediol, ethylene glycol, trimethylene glycol, pentamethylene glycol, hexamethylene glycol, neopentyl glycol, and decamethylene glycol, alicyclic diols such as 1,1-cyclohexanedimethanol, 1,4-dicyclohexanedimethanol, and tricyclodecane dimethanol, and aromatic diols such as xylylene glycol, bis(p-hydroxy)diphenyl, bis(p-hydroxy)diphenylpropane, 2,2'-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxyethoxy)phenyl]sulfone, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 4,4'-dihydroxy-p-terphenyl, and 4,4'-dihydroxy-p-quarterphenyl, and such diols can also be used in the form of ester-forming derivatives, for example, acetylated forms, alkali metal salts, and the like.

[0026] The soft segment used in the present invention is an aliphatic polyether and / or an aliphatic polyester. Examples of the aliphatic polyether include poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(trimethylene oxide) glycol, poly(tetramethylene oxide) glycol, poly(hexamethylene oxide) glycol, a copolymer of ethylene oxide and propylene oxide, an ethylene oxide adduct of poly(propylene oxide) glycol, and a copolymer of ethylene oxide and tetrahydrofuran. Among these, poly(tetramethylene oxide) glycol and / or an ethylene oxide adduct of poly(propylene oxide) glycol and / or a copolymer of ethylene oxide and tetrahydrofuran are preferably used. Examples of the aliphatic polyester include poly(ε-caprolactone), polyenantholactone, polycaprylolactone, polybutylene adipate, and polyethylene adipate.

[0027] Among these aliphatic polyethers and / or aliphatic polyesters, from the viewpoint of the elastic properties of the resulting polyester block copolymer, poly(tetramethylene oxide) glycol, an ethylene oxide adduct of poly(propylene oxide) glycol, a copolymer glycol of ethylene oxide and tetrahydrofuran, poly(ε-caprolactone), polybutylene adipate, polyethylene adipate, etc. are preferred, and among these, poly(tetramethylene oxide) glycol, an ethylene oxide adduct of poly(propylene oxide) glycol, and a copolymer glycol of ethylene oxide and tetrahydrofuran are particularly preferred. The number average molecular weight of these soft segments in the copolymerized state is preferably 300 to 6000, more preferably 1000 to 3000, and even more preferably 1000 to 2000.

[0028] The thermoplastic polyester elastomer resin (A) in the present invention comprises, as its constituent components, a hard segment (H) consisting of a crystalline aromatic polyester unit and a soft segment (L) consisting of an aliphatic polyether unit and / or an aliphatic polyester unit.

[0029] In the thermoplastic polyester elastomer resin (A) of the present invention, the hard segment (H) may be composed of two or more types of acid components and one or more types of diol components.

[0030] A preferred example of the hard segment (H) is one that is composed of polybutylene terephthalate units derived from terephthalic acid and / or dimethyl terephthalate, and polybutylene isophthalate units derived from isophthalic acid and / or dimethyl isophthalate and 1,4-butanediol. By using the polyester block copolymer (A2) that uses two or more types of acid components, the dispersibility of the first electromagnetic shielding material (B) and the second electromagnetic shielding material (C) in the resulting polyester elastomer resin composition can be improved, and the electromagnetic wave absorption properties of the electromagnetic shielding material obtained by molding the thermoplastic polyester elastomer resin composition can be improved, and the warping of the electromagnetic shielding material thus obtained can be further reduced.

[0031] The soft segment (L) is selected from the aliphatic polyethers and / or aliphatic polyesters described above.

[0032] The polyester block copolymer (A2) contains 40 to 85 mass % of the hard segment (H) and 15 to 60 mass % of the soft segment (L1), and preferably contains 50 to 80 mass % of the hard segment (H) and 20 to 50 mass % of the soft segment (L).

[0033] The polyester block copolymer (A2) has a melting point of preferably 150° C. to 225° C., more preferably 160° C. to 220° C. If the polyester block copolymer (A2) has a melting point higher than 225° C., the flexibility and impact resistance of the resulting thermoplastic polyester elastomer resin composition will be insufficient, whereas if the melting point is lower than 150° C., the strength and elastic modulus of the resulting thermoplastic polyester elastomer resin composition will be insufficient, making it difficult to satisfy excellent flexibility, impact resistance and mechanical strength, which is undesirable.

[0034] The polyester block copolymer (A2) used in the present invention can be produced by a known method.Specific examples thereof include a method of transesterifying a lower alcohol diester of a dicarboxylic acid with an excess of a low molecular weight glycol and a soft segment component in the presence of a catalyst, and polycondensing the resulting reaction product, and a method of esterifying a dicarboxylic acid with an excess of a glycol and a soft segment component in the presence of a catalyst, and polycondensing the resulting reaction product, and any of these methods may be used.

[0035] Next, the thermoplastic polyester elastomer resin of the present invention may contain other thermoplastic resins other than polyester elastomers, such as olefin resins, polyamide resins, polyester resins other than thermoplastic polyester elastomers, polyurethane resins, polycarbonate resins, polystyrene resins, polyacrylonitrile resins (AS resins), polyacrylonitrile styrene resins (ABS resins), acrylic resins, polymethyl methacrylate resins, epoxy resins, and phenoxy resins.

[0036] Specific examples of olefin resins include ethylene / propylene copolymers, ethylene / propylene / non-conjugated diene copolymers, ethylene-butene-1 copolymers, ethylene / glycidyl methacrylate copolymers, ethylene / butene-1 / maleic anhydride copolymers, ethylene / propylene / maleic anhydride copolymers, and ethylene / maleic anhydride copolymers. Specific examples of polyamide resins include polyamide 6, polyamide 66, polyamide 610, polyamide 12, polyamide 11, polyamide 410, and polyamide 46, and copolymers thereof may also be used in combination. As the polyester resin, not only the thermoplastic polyester elastomers described above but also known thermoplastic polyester resins may be used, and polyethylene terephthalate resins and polybutylene terephthalate resins may be preferably used. In addition, the acid component and diol component similar to those of the thermoplastic polyester elastomers may be included as copolymers.

[0037] The purposes of including thermoplastic resins other than polyester elastomers include adjusting melt processability and flowability, improving dispersibility and compatibility of various additives, adjusting flexibility and elastic modulus, improving heat resistance and heat aging resistance, and improving chemical resistance.

[0038] The amount of the thermoplastic resin other than the polyester elastomer is preferably 1 to 20 parts by weight, more preferably 5 to 10 parts by weight, based on 100 parts by weight of the polyester block copolymer (A2). If it is less than 1 part by weight, the combined effect of the thermoplastic resin used in combination is limited, and if it exceeds 20 parts by weight, the dispersibility of the polyester elastomer and the other thermoplastic resin decreases, and the flexibility, mechanical properties, moldability, etc., inherent to the thermoplastic polyester elastomer resin composition of the present invention are impaired, which is undesirable.

[0039] [First electromagnetic wave shielding material (B)] The thermoplastic polyester elastomer resin of the present embodiment contains carbon nanotubes as the first electromagnetic wave shielding material (B). By containing carbon nanotubes, it is possible to impart electromagnetic wave absorbing properties to the thermoplastic polyester elastomer resin composition.

[0040] The carbon nanotubes used in this embodiment are single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and preferably contain at least multi-walled carbon nanotubes from the viewpoint of electromagnetic wave absorption properties. In addition, carbon materials having a carbon nanotube structure in part can also be used. In addition, the carbon nanotubes are not limited to a cylindrical shape, and may have a coil shape in which the spiral turns at a pitch of 1 μm or less. Carbon nanotubes are available as commercially available products, and examples of such carbon nanotubes include carbon nanotubes available from Bayer MaterialScience, Nanosil, Showa Denko K.K., and Hyperion Catalysis International. In addition to the name carbon nanotubes, they are also called graphite fibrils, carbon fibrils, etc. The diameter (number average fiber diameter) of the carbon nanotubes is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. In addition, the diameter (number average fiber diameter) of the carbon nanotubes is preferably 30 nm or less, and even more preferably 20 nm or less. It is preferable that the diameter of the carbon nanotubes is within the above range, since dispersibility and processability are improved.

[0041] The carbon nanotubes may be blended in the form of a masterbatch. In this case, the concentration of the carbon nanotubes in the masterbatch is preferably 1% by mass or more, more preferably 5% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and even more preferably 20% by mass or less. By setting the concentration within the range of the upper limit or less and the lower limit or more, the dispersibility of the carbon nanotubes in the thermoplastic polyester elastomer resin (A) is further improved. The resin used in the masterbatch is exemplified by the thermoplastic polyester elastomer resin (A). That is, in the thermoplastic polyester elastomer resin composition of this embodiment, at least a part of the thermoplastic polyester elastomer resin (A) is preferably derived from the masterbatch of the carbon nanotubes.

[0042] The content of carbon nanotubes in the thermoplastic polyester elastomer resin composition of the present embodiment is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, may be 0.2% by mass or more, or may be 0.4% by mass or more. By making the content of carbon nanotubes in the thermoplastic polyester elastomer resin composition equal to or more than the lower limit, electromagnetic wave absorption properties are effectively exhibited. In addition, the content of carbon nanotubes in the thermoplastic polyester elastomer resin composition of the present embodiment is preferably 10% by mass or less, more preferably 8% by mass or less, even more preferably 6% by mass or less, even more preferably 4% by mass or less, even more preferably 3% by mass or less, may be 2% by mass or less, or may be 1% by mass or less. By making the content of carbon nanotubes in the thermoplastic polyester elastomer resin composition equal to or less than the upper limit, the flowability of the resin is further improved.

[0043] The thermoplastic polyester elastomer resin composition of the present embodiment may contain only one type of carbon nanotube, or may contain two or more types. When two or more types are contained, the total amount of the carbon nanotubes is preferably within the above range.

[0044] [Second electromagnetic shielding material (C)] The thermoplastic polyester elastomer resin of the present embodiment contains carbon black as the second electromagnetic wave shielding material (C). By containing carbon black, it is possible to impart electromagnetic wave absorbing properties to the thermoplastic polyester elastomer resin composition.

[0045] The carbon black used in this embodiment may be furnace black produced by continuously pyrolyzing a gaseous or liquid raw material in a reactor, particularly ketjen black produced from ethylene heavy oil, channel black produced by burning a raw material gas and applying the flame to the bottom surface of a channel steel to rapidly cool and precipitate, thermal black produced by periodically repeating combustion and pyrolysis of a gas as a raw material, and acetylene black produced from acetylene gas as a raw material, either alone or in combination of two or more of the above. Carbon black is available as a commercially available product, and examples of the carbon black include carbon black available from Mitsubishi Chemical Corporation, Nippon Steel Carbon Corporation, Tokai Carbon Corporation, Cabot Corporation, and the like. The average primary particle size of the carbon black is preferably 20 nm or more, more preferably 25 nm or more. The average primary particle size of the carbon black is preferably 40 nm or less, and more preferably 35 nm or less. The content of carbon black in the thermoplastic polyester elastomer resin composition of this embodiment is preferably 3 mass% or more, more preferably 5 mass% or more, and even more preferably 7 mass% or more. By making the carbon black content in the thermoplastic polyester elastomer resin composition equal to or more than the lower limit, electromagnetic wave absorbing properties are effectively exhibited. In addition, the carbon black content in the thermoplastic polyester elastomer resin composition of the present embodiment is preferably equal to or less than 20 mass%, more preferably equal to or less than 15 mass%, and even more preferably equal to or less than 12 mass%. By making the carbon black content in the thermoplastic polyester elastomer resin composition equal to or less than the upper limit, the flowability of the resin tends to be further improved.

[0046] [Dispersant (D)] The dispersant that can be contained in the thermoplastic polyester elastomer resin composition of this embodiment can be any one of natural wax, semi-synthetic wax, synthetic wax, and aliphatic metal salt, and can be any one of paraffin wax, montan wax, amide wax, ethylene bisstearic acid amide, fatty acid metal salt, silicone, polyolefin wax, etc., or any combination of several of these.

[0047] Examples of natural waxes include paraffin wax and montan wax, examples of semi-synthetic waxes include ethylene bisstearic acid amide and amide wax, and examples of synthetic waxes include polyethylene wax and polypropylene wax. The number average molecular weight of the wax is preferably 1,000 to 30,000, and more preferably 1,000 to 1,0000. When the number average molecular weight of the wax is 1,000 or more, the wettability of the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) is improved when the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) are kneaded with the thermoplastic polyester elastomer resin (A), and this is preferable because the first electromagnetic wave shielding material (B) can be particularly dissolved. When the number average molecular weight of the wax is 30,000 or less, the wax has an appropriate melt viscosity during kneading, and can be kneaded with a higher shear force. This makes it possible to dissolve the first electromagnetic wave shielding material (B) while suppressing re-agglomeration, and the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) become highly dispersed, thereby improving the electromagnetic wave absorption performance, which is preferable.

[0048] Examples of the aliphatic metal salt include metal salts of linear aliphatic monocarboxylic acids such as lauric acid, palmitic acid, stearic acid, oleic acid, and ricinoleic acid. Examples of the counter cations for the metal salt include calcium, zinc, magnesium, barium, and aluminum.

[0049] The content of the wax and the aliphatic metal salt is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 15 parts by mass, based on 100 parts by mass of the thermoplastic polyester elastomer resin (A). When the content is 0.1 part by mass or more, the dispersibility of the first electromagnetic shielding material (B) and the second electromagnetic shielding material (C) can be further improved, and when the content is 30 parts by mass or less, optimal fluidity can be maintained, and an appropriate shear force can be applied to the first electromagnetic shielding material (B) during kneading, thereby further improving the dispersibility of the first electromagnetic shielding material (B) and the second electromagnetic shielding material (C).

[0050] [Amorphous resin] The thermoplastic polyester elastomer resin (A) may contain 10 to 80 parts by mass of an amorphous resin based on 100 parts by mass of the thermoplastic polyester elastomer resin (A).

[0051] The amorphous resin used in the present invention is selected from a group of amorphous resins having a glass transition temperature of not more than 160° C. The amorphous resin is preferably at least one selected from polycarbonate resin, ABS resin, AS resin, and PMMA resin.

[0052] A non-crystalline resin that can be effectively used in the present invention includes polycarbonate resin. Examples of polycarbonate resin include aromatic dihydroxy compounds or carbonate polymers obtained by reacting a small amount of a polyhydroxy compound with phosgene or a carbonic acid diester. Examples of aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl)propane (referred to as bisphenol A), tetramethyl bisphenol A, bis(4-hydroxyphenyl)-p-diisopropylbenzene, hydroquinone, resorcinol, and 4,4-dihydroxydiphenyl, and bisphenol A is preferably used.

[0053] The amount of the polycarbonate resin to be added is preferably 10 to 80 parts by mass, and more preferably 10 to 30 parts by mass, per 100 parts by mass of the thermoplastic polyester elastomer resin (A).

[0054] As an example of an amorphous resin that can be effectively used in the present invention, a diene copolymer can be preferably used. Among them, it is preferable to contain an aromatic vinyl monomer and a vinyl cyanide monomer as the main components. It can further contain other types of vinyl monomers. As another embodiment, there is a graft polymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer in the presence of a diene rubber polymer. It can further contain other types of vinyl monomers.

[0055] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, p-methylstyrene, and pt-butylstyrene, with styrene being preferred among them. Examples of cyanide vinyl monomers include acrylonitrile and methacrylonitrile, with styrene being preferred among them. Examples of diene rubber polymers include polybutadiene, styrene-butadiene copolymers, and acrylonitrile-butadiene copolymers, which have good moldability and dispersibility with polyester block copolymers, and one or more of these can be used. Specifically, acrylonitrile-butadiene-styrene copolymers (ABS resins) and acrylonitrile-styrene copolymers (AS resins) can be preferably used.

[0056] The copolymerization ratio in the ABS resin used in the present invention is preferably 40 to 85 parts by weight of the rubber polymer and 15 to 60 parts by weight of the aromatic vinyl monomer and the vinyl cyanide monomer. If the rubber polymer exceeds 85 parts by weight, the graft ratio decreases, and good mechanical properties as a thermoplastic polyester elastomer resin cannot be obtained. Furthermore, if it is less than 40 parts by weight or exceeds 85 parts by weight, the compatibility with the polyester block copolymer decreases, and the processability decreases.

[0057] The proportion of aromatic vinyl monomer in the diene copolymer is preferably 50-99% by mass, more preferably 60-90% by mass, and even more preferably 70-80% by mass, based on the total vinyl monomers, and the proportion of cyanide vinyl monomer is preferably 1-50% by mass, more preferably 10-40% by mass, and even more preferably 20-30% by mass. If the proportion of aromatic vinyl monomer exceeds 99% by mass or is less than 50% by mass, or if the proportion of cyanide vinyl monomer exceeds 50% by mass or is less than 1% by mass, the compatibility with the polyester block copolymer decreases, and good mechanical properties may not be obtained. In addition, it is preferable to use other vinyl monomers copolymerizable with these at 50% by mass or less.

[0058] Although ABS resin and AS resin are exemplified as diene copolymers, other vinyl monomers may be copolymerized within the scope of not impairing the effects of the present invention. Examples of other copolymerizable vinyl monomers include α,β-unsaturated carboxylic acid anhydrides such as maleic anhydride and itaconic anhydride, and imide compounds of α,β-unsaturated dicarboxylic acids such as N-phenylmaleimide, N-methylmaleimide, and Nt-butylmaleimide.

[0059] The blending amount of the ABS resin and the AS resin is preferably 10 to 80 parts by mass, and more preferably 10 to 50 parts by mass, per 100 parts by mass of the thermoplastic polyester elastomer resin (A).

[0060] Examples of other copolymerizable monomers include α,β-unsaturated carboxylic acids such as acrylic acid and methacrylic acid, and α,β-unsaturated carboxylic acid esters such as methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and cyclohexyl methacrylate. Among these, polymethyl methacrylate (PMMA resin), which is a polymer of methyl methacrylate, can be preferably used.

[0061] Specific examples of the vinyl resin include vinyl copolymers such as methyl methacrylate / styrene resin (MS resin), methyl methacrylate / acrylonitrile resin, polystyrene resin, and styrene / butadiene resin, block copolymers such as acrylonitrile / butadiene / methyl methacrylate / styrene resin (MABS resin), styrene / butadiene / styrene resin, styrene / isoprene / styrene resin, and styrene / ethylene / butadiene / styrene resin; and multilayer structures of dimethylsiloxane / butyl acrylate polymer (core layer) and methyl methacrylate polymer (shell layer), multilayer structures of dimethylsiloxane / butyl acrylate polymer (core layer) and acrylonitrile / styrene copolymer (shell layer), multilayer structures of butadiene / styrene polymer (core layer) and methyl methacrylate polymer (shell layer), and core-shell rubbers of butadiene / styrene polymer (core layer) and acrylonitrile / styrene copolymer (shell layer). These may be used alone or in mixtures of two or more types.

[0062] Other examples of amorphous resins that can be effectively used in the present invention include epoxy resins and phenoxy resins. Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, glycidyl ether type epoxy compounds which are polycondensates of phenolic compounds and epichlorohydrin, glycidyl ester type epoxy compounds such as phthalic acid glycidyl ester, glycidyl amine type epoxy compounds such as N,N'-methylenebis(N-glycidylaniline), phenol novolac type epoxy resins, cresol novolac type epoxy resins, naphthol novolac type epoxy resins, naphthol cresol novolac type epoxy resins, biphenylene novolac type epoxy resins, dicyclopentadiene type epoxy resins, polyfunctional biphenyl aralkyl type epoxy resins, and imide ring-containing bisphenol type epoxy resins. Two or more of these may be blended. Phenoxy resins are polyhydroxy polyethers synthesized from bisphenols and epichlorohydrin, and examples thereof include bisphenol A type phenoxy resins and bisphenol F type phenoxy resins whose terminal groups are hydroxyl groups.

[0063] The amount of epoxy resin and phenoxy resin blended is preferably 10 to 80 parts by weight, more preferably 10 to 20 parts by weight, based on 100 parts by weight of the thermoplastic polyester elastomer resin (A). If the amount is less than 10 parts by weight, sufficient effect cannot be obtained, and if the amount exceeds 80 parts by weight, moldability deteriorates due to a significant increase in viscosity, and dispersibility of the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) in the molded product deteriorates, resulting in deterioration of the electromagnetic wave absorption property of the molded product.

[0064] Glycidyl ether epoxy compounds are preferred from the viewpoint of suppressing decomposition during melt processing and compatibility with thermoplastic polyester elastomer resins, and bisphenol A epoxy compounds are preferred from the viewpoint of improving heat resistance. Furthermore, among bisphenol A epoxy compounds, bisphenol A epoxy resins with an epoxy value of 500 to 5000 g / eq are preferred. When the epoxy value of the bisphenol A epoxy resin is 500 g / eq or less, it is not preferred because the possibility of rapid viscosity increase during melt processing increases. When the epoxy value of the bisphenol A epoxy resin is 5000 g / eq or more, it is not preferred from the viewpoint of improving heat resistance and hydrolysis resistance. From the viewpoint of long-term improvement of heat resistance without impairing processability during melting, phenol novolac epoxy resins, especially dicyclopentadiene epoxy resins, are preferred. The epoxy value of multifunctional phenol novolac and dicyclopentadiene epoxy resins is preferably 150 to 300 g / eq. When the epoxy value of the multifunctional phenol novolac type epoxy resin is 150 g / eq or less, the crosslink density becomes high in a high temperature environment, which is undesirable because it impairs the toughness of the polyester elastomer.

[0065] [Thermoplastic styrene elastomer] In the present invention, a thermoplastic styrene-based elastomer having an aromatic vinyl unit content of 20 to 50% by mass can be used. It is preferable that the thermoplastic styrene-based elastomer is contained in an amount of 5 to 60 parts by mass per 100 parts by mass of the thermoplastic polyester elastomer resin (A). The thermoplastic styrene elastomer is composed of a polystyrene block and a soft elastomer block in a hard segment, and is a block copolymer having a plurality of block portions such as a diblock or triblock. Examples of the styrene elastomer include polystyrene-poly(ethylene / butylene) block-polystyrene (SEBS), polystyrene-poly(ethylene / propylene) block-polystyrene (SEPS), and polystyrene-poly(ethylene-ethylene / propylene) block-polystyrene (SEEPS). Among these, polystyrene-poly(ethylene / butylene) block-polystyrene (SEBS) is preferably used from the viewpoint of dispersibility in the thermoplastic polyester elastomer.

[0066] The content of the styrene block unit in the thermoplastic styrene-based elastomer is preferably 20 to 50 mass%, more preferably 30 to 40 mass%. If the content of the styrene block unit is less than 20 mass%, this is not preferred from the viewpoint of suppressing the molding shrinkage of the resulting thermoplastic polyester elastomer, and if the content of the styrene block unit is more than 50 mass%, this is not preferred since the flexibility of the thermoplastic polyester elastomer is impaired.

[0067] The weight average molecular weight of the thermoplastic styrene elastomer is preferably 100,000 to 300,000, more preferably 200,000 to 300,000. The weight average molecular weight of the thermoplastic styrene elastomer in the above range is preferable from the viewpoint of promoting the compatibility between the thermoplastic polyester elastomer and the amorphous resin during melt kneading with the amorphous resin in addition to the dispersibility in the thermoplastic polyester elastomer, and the dispersibility of the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) in the thermoplastic polyester elastomer is improved, so that the electromagnetic wave absorption properties of the molded product can be improved. If the weight average molecular weight of the thermoplastic styrene elastomer is less than 100,000, the balance between the mechanical strength and flexibility of the obtained thermoplastic polyester elastomer resin is deteriorated, which is not preferable. If the weight average molecular weight of the thermoplastic styrene elastomer is more than 300,000, the dispersibility in the thermoplastic polyester elastomer is deteriorated, and the processability during melt extrusion is reduced, which is not preferable.

[0068] [Polyamide copolymer] The polyamide copolymer used in the present invention is a polymeric compound having an amide bond in the molecular chain, and examples thereof include polymers from lactams, polymers of salts obtained by reacting adipic acid, sebacic acid, dodecanedioic acid, etc. with ethylenediamine, hexamethylenediamine, metaxylenediamine, etc., or polymers from ω-aminocarboxylic acids. These polyamide resins may be copolymers, or two or more different polymers may be used in combination. Examples include copolymers such as polyamide 6 / polyamide 610, polyamide 6 / polyamide 610 / polyamide 12, polyamide 6 / polyamide 12, polyamide 6 / polyamide 66 / polyamide 12, and polyamide 6 / polyamide 66 / polyamide 610. Among the polyamide resins, when polyamide 6 and / or a binary or ternary or higher copolymer polyamide resin is used, a ternary copolymer of polyamide 6 / polyamide 66 / polyamide 610 can be used preferably.

[0069] The amount of the polyamide copolymer is preferably 0.5 to 10 parts by mass, more preferably 1 to 7 parts by mass, and further preferably 1.5 to 5 parts by mass, based on 100 parts by mass of the thermoplastic polyester elastomer resin (A). If the amount of the polyamide copolymer (C) is less than 0.5 parts by mass, the degree of the desired improving effect is small, and if it exceeds 10 parts by mass, the inherent flexibility and flex fatigue resistance of the thermoplastic polyester elastomer resin are impaired, which is not preferable.

[0070] [Antioxidants] The thermoplastic polyester elastomer resin of the present invention can have improved heat resistance by further adding an antioxidant. The antioxidant used in the present invention may be one or a combination of two or more selected from the group consisting of aromatic amine antioxidants, hindered phenol antioxidants, sulfur antioxidants, and phosphorus antioxidants.

[0071] Specific examples of aromatic amine-based antioxidants include phenylnaphthylamine, 4,4'-dimethoxydiphenylamine, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and 4-isopropoxydiphenylamine, and among these, the use of diphenylamine-based compounds is preferred.

[0072] Specific examples of hindered phenol-based antioxidants include 2,4-dimethyl-6-t-butylphenol, 2,6-di-t-butylphenol, 2,6-di-t-butyl-p-cresol, hydroxymethyl-2,6-di-t-butylphenol, 2,6-di-t-α-dimethylamino-p-cresol, 2,5-di-t-butyl-4-ethylphenol, 4,4'-bis(2,6-di-t-butylphenol), 2,2'-methylene-bis-4-methyl-6-t-butylphenol, and 2,2'-methylene-bis(4-ethyl-6-t-butylphenol). ), 4,4'-methylene-bis(6-t-butyl-o-cresol), 4,4'-methylene-bis(2,6-di-t-butylphenol), 2,2'-methylene-bis(4-methyl-6-cyclohexylphenol), 4,4'-butylidene-bis(3-methyl-6-t-butylphenol), 4,4'-thiobis(6-t-butyl-3-methylphenol), bis(3-methyl-4-hydroxy-5-t-butylbenzyl)sulfide, 4,4'-thiobis(6-t-butyl-o-cresol), 2,2'-thiobis(4-methyl-6-t-butylphenol) 2,6-bis(2'-hydroxy-3'-t-butyl-5'-methylbenzyl)-4-methylphenol, diethyl ester of 3,5-di-t-butyl-4-hydroxybenzenesulfonic acid, 2,2'-dihydroxy-3,3'-di(α-methylcyclohexyl)-5,5'-dimethyl-diphenylmethane, α-octadecyl-3(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, 6-(hydroxy-3,5-di-t-butylanilino)-2,4-bis-octyl-thio-1,3,5-triazine, hexamethyl N,N'-Hexamethylene-bis(3,5-di-t-butyl-4-hydroxyhydrocinnamic acid amide), 2,2-thio[diethyl-bis-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate], dioctadecyl ester of 3,5-di-t-butyl-4-hydroxybenzenephosphonic acid, tetrakis[methylene-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, 1,3,5-trimethyl-2,4,Examples of such compounds include 6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, 1,1,3-tris(2-methyl-4-hydroxy-5-di-t-butylphenyl)butane, tris(3,5-di-t-butyl-4-hydroxyphenyl)isocyanurate, and tris[β-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl-oxyethyl]isocyanurate. Among these, it is particularly preferable to use compounds having a molecular weight of 500 or more, such as tetrakis[methylene-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane.

[0073] The sulfur-based antioxidants are compounds containing sulfur, such as thioethers, dithioacid salts, mercaptobenzimidazoles, thiocarbanilides, and thiodipropionates. Among these, it is particularly preferable to use thiodipropionates.

[0074] The phosphorus-based antioxidants are compounds containing phosphorus, such as phosphoric acid, phosphorous acid, hypophosphorous acid derivatives, phenylphosphonic acid, polyphosphonates, dialkyl pentaerythritol diphosphites, and dialkyl bisphenol A diphosphites. Among these, it is preferable to use a compound having both a phosphorus atom and a sulfur atom in the molecule, or a compound having two or more phosphorus atoms in the molecule.

[0075] The total amount of these antioxidants is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 4 parts by mass, and even more preferably 0.3 to 3 parts by mass, based on 100 parts by mass of the thermoplastic polyester elastomer resin. By making the total amount of antioxidants 0.05 parts by mass or more, heat resistance is improved. In addition, by making the total amount of antioxidants 5 parts by mass or less, blooming from the molded article obtained by molding the thermoplastic polyester elastomer resin composition of the present invention is less likely to occur, and this is preferable from the viewpoint of suppressing the decrease in mechanical strength and heat resistance of the molded article obtained by molding the thermoplastic polyester elastomer resin composition of the present invention.

[0076] [Ultraviolet absorber] The thermoplastic polyester elastomer resin of the present embodiment may contain an ultraviolet absorbing agent as necessary to improve weather resistance. Examples of ultraviolet absorbing agents include benzotriazoles: 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole, 2-[5-chloro-(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol, and benzophenones: 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone. The preferred amount of ultraviolet absorbing agent added is 0.1 to 2.0 parts by mass, more preferably 0.5 to 1.0 parts by mass, relative to 100 parts by mass of the thermoplastic polyester elastomer resin.

[0077] [Hindered amine compounds] The thermoplastic polyester elastomer resin of the present embodiment may contain a hindered amine compound as necessary to improve weather resistance. Examples of the hindered amine compound (E) include NR-type tertiary amine bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, and N-OR-type amine 2,4-bis[N-butyl-N-(1-cyclohexyl-2,2,6,6-tetramethylpiperidic-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-tetrazine. The preferred amount of the hindered amine compound to be added is 0.1 to 2.0 parts by mass, and more preferably 0.5 to 1.0 parts by mass, relative to 100 parts by mass of the thermoplastic polyester elastomer resin.

[0078] [Other additives] Furthermore, the thermoplastic polyester elastomer resin composition of the present invention may contain, as necessary, within the scope not impairing the object, antioxidants (phosphonite compounds, phosphorous compounds, hypophosphorous compounds, hindered phenol compounds, thioether compounds, etc.), antistatic agents (polyether ester amides, etc.), lubricants (stearyl alcohol, metal stearates, stearic acid amides, glyceride stearates, etc.), dyes (organic dyes such as nigrosine), pigments (titanium dioxide and various inorganic pigments, organic pigments, etc.), plasticizers (phthalic acid, adipic acid, trimellitic acid, etc.), etc. Additives such as tackiness improvers, quenchers, metal deactivators, and the like, and transesterification inhibitors may be added. Additives widely used as additives may be added within the scope of the present invention without impairing the characteristics of the present invention.

[0079] [Molded body] The thermoplastic polyester elastomer resin composition of the present invention can be molded into a thermoplastic polyester elastomer resin molded article using a commonly used molding machine such as injection molding, blow molding, extrusion molding, compression molding, extrusion film formation, T-die film formation, and calendar film formation. Among them, molding by injection molding is preferable. The shape of the molded thermoplastic polyester elastomer resin is not particularly limited, but can be selected depending on the molding method, etc., and may be any one-dimensional shape (e.g., linear, rod-like, etc.), two-dimensional shape (e.g., sheet-like, frame-like, film-like, etc.), or three-dimensional shape (e.g., a shape having a recess, a protrusion, or an uneven portion, a tube shape, a hose shape, etc.).

[0080] The thermoplastic polyester elastomer resin molded article of the present invention may be a composite molded article obtained by insert molding, hybrid molding, two-color molding, etc., of a member (hereinafter sometimes simply referred to as "member 1") formed by molding the thermoplastic polyester elastomer resin composition of the present invention and a member (hereinafter sometimes simply referred to as "member 2") formed of another hard resin and another material having a higher elastic modulus (Young's modulus) than the thermoplastic polyester elastomer resin composition of the present invention. More than half of member 1 is composed of the thermoplastic polyester elastomer resin composition of the present invention, but it may contain other resin materials.

[0081] In the composite molded product, the members 1 and 2 may be bonded via an adhesive layer, but are preferably bonded directly without an adhesive layer. Methods for integrating the members 1 and 2 include a method in which the joining surface of the inserted member 2 is subjected to physical and chemical treatments to improve the adhesion between the members 1 and 2. Another method is to provide a claw- or folded-back fixed fitting portion as the structure of the member 1, and to fix both members via this fixed fitting portion. Furthermore, the members 1 and 2 may be fixed using screws or the like.

[0082] The shape of the thermoplastic polyester elastomer resin molded article or composite molded article in the present invention means that the thickness of a portion that accounts for 80% or more of the total is 5.0 mm or less, and the thickness of the thin portion is preferably 0.5 mm to 3.0 mm, and more preferably 1.0 mm to 2.0 mm.

[0083] The electromagnetic shielding material of the present embodiment is preferably used as an electromagnetic wave absorbing member formed from a thermoplastic polyester elastomer resin composition, more preferably for an electromagnetic wave shielding member having an electromagnetic wave frequency of 60 GHz to 90 GHz, and even more preferably for an electromagnetic wave shielding member having an electromagnetic wave frequency of 70 GHz to 80 GHz. Such an electromagnetic shielding material is used for a housing or cover of an automobile-mounted millimeter wave radar. The electromagnetic shielding material of the present embodiment can be suitably used in an automobile-mounted millimeter wave radar, a railway / aviation millimeter wave radar, a millimeter wave radar for traffic infrastructure, a millimeter wave radar for various security devices, a millimeter wave radar for medical / nursing care, a millimeter wave radar for network transmission, and the like. EXAMPLES

[0084] The effects of the present invention will be described below with reference to examples. In the examples, % and parts are all by mass unless otherwise specified. Furthermore, the physical properties shown in the examples were measured as follows.

[0085] [Melting point] Using a differential scanning calorimeter (DSC Q1000 manufactured by TA Instruments), a 10 mg sample of the thermoplastic polyester elastomer resin composition was measured in a nitrogen gas atmosphere at a heating and cooling rate of 10°C / min. The temperature at the extreme value of the obtained melting endothermic curve was determined as the melting point, and the temperature at the extreme value of the crystallization exothermic curve was determined as the crystallization temperature.

[0086] [Temperature showing maximum value of loss factor tan δ] Using a dynamic viscoelasticity measuring device RSAIII manufactured by TA Instruments, dynamic viscoelasticity was measured in tensile mode under the following conditions in accordance with the test standard JIS K7244-1;1998 (ISO6721-1). The loss factor tan δ was evaluated using the obtained storage modulus E' and loss modulus E'' values. tan δ = (loss modulus E'') / (storage modulus E') Measurement temperature range: -100℃ to 200℃ (below the melting point of the resin composition) Temperature rise: 10 / min Measurement frequency: 10Hz

[0087] Here, among the temperatures showing the maximum value of the loss factor tan δ, the peak temperature shown by the main component polymer in the resin composition was taken as the temperature showing the maximum value of the loss factor in the examples of the thermoplastic resin composition. The temperature showing the maximum value of the loss factor tan δ is preferably 20°C or less, more preferably 0°C or less, even more preferably -20°C or less, and even more preferably -40°C or less. By showing the maximum value of the loss factor tan δ at a temperature of 20°C or less, the thermoplastic polyester elastomer resin composition in this embodiment has excellent impact resistance from room temperature to low temperature, and can achieve both good mechanical properties and electromagnetic wave absorption properties.

[0088] [Surface hardness (Shore D scale)] According to the method described in JIS K7215:1986 (ISO 868), the surface hardness of the thermoplastic polyester elastomer resin composition sample was measured in a temperature controlled environment of 23°C and 50% RH. In the case of hard resins that cannot be expressed in the range of values ​​from 0 to 100 on the Shore D scale, the Rockwell hardness value was expressed as the value of the R scale (e.g., R100) and the M scale (e.g., MR80) according to the method described in JIS Z2245.

[0089] [Mechanical properties (tensile elongation at break)] Using an injection molding machine NEX1000 manufactured by Nissei Plastics Co., Ltd., a sample of the polyester elastomer resin composition of the present invention was injection molded under the conditions of a molding temperature of 200°C, a mold temperature of 40°C, a molding cycle of a total injection time and pressure holding time of 10 seconds, and a cooling time of 30 seconds to obtain a JIS No. 2 test piece (dumbbell test piece). For compositions in which the melting point of the polyester elastomer exceeds 200°C, molding was performed at the melting point of the polyester elastomer + 20°C.

[0090] The tensile elongation at break was measured in accordance with JIS K7161-1:2014 using the obtained JIS No. 2 test piece. The tensile elongation at break was 200 mm / min. The tensile elongation at break obtained differs depending on the type of thermoplastic polyester elastomer used, but the tensile elongation at break (%) obtained in the molded state of the JIS No. 2 test piece is preferably 100% or more. Furthermore, the tensile elongation at break (%) is more preferably 200% or more, and even more preferably 300% or more. By making the tensile elongation at break (%) of the JIS No. 2 test piece 100% or more, the thermoplastic polyester elastomer resin composition in this embodiment has excellent toughness and can achieve both good mechanical properties and electromagnetic wave absorption properties.

[0091] [Melt viscosity characteristics (MFR)] According to ASTM D1238, the melt mass flow rate (MFR) of the sample of the thermoplastic elastomer resin composition in this embodiment is measured at a load of 2160 g at a set temperature of 200° C. for a thermoplastic elastomer resin composition having a melting point of less than 180° C., and at a set temperature of melting point + 30° C. for a thermoplastic elastomer resin composition having a melting point of 200° C. or more. The MFR is preferably 1.0 g / 10 min or more and less than 40 g / 10 min. More preferably, it is 5.0 g / 10 min or more and less than 30 g / 10 min, and even more preferably, it is 10 g / 10 min or more and less than 25 g / 10 min. By having the MFR of the thermoplastic elastomer resin composition in this embodiment being 1.0 g / 10 min or more and less than 40 g / 10 min, it is possible to reduce the thickness and have good melt processability, and it is possible to achieve both high melt processability and electromagnetic wave absorption properties.

[0092] [Low temperature impact resistance] The sample of the thermoplastic elastomer resin composition of the present invention preferably has an Izod impact strength of 100 J / m notch or more, more preferably 150 J / m notch or more, and even more preferably 200 J / m notch or more, when measured according to the method described in JIS K7110:1999 under the condition that the temperature of the notched Izod impact test piece during measurement is -20°C and 23°C. In particular, from the viewpoint of excellent toughness and impact resistance properties of the molded article using the thermoplastic elastomer resin composition, it is even more preferable that the NB (no break) is 1000 J / m notch or more. By having the Izod impact strength of 100 J / m or more, or even NB, the molded article using the thermoplastic elastomer resin composition of the present invention can achieve both good impact resistance over a wide range from low to high temperatures and electromagnetic wave absorption properties.

[0093] [Surface resistivity] A sample of the thermoplastic polyester elastomer resin composition was dried in a hot air oven at 90°C for 4 hours, and injection molded in an injection molding machine NEX1000 manufactured by Nissei Plastics Industries Co., Ltd. with a cylinder setting temperature of the melting point of the thermoplastic polyester elastomer resin composition + 30°C and a mold temperature of 50°C. A square plate prepared to 80mm x 80mm x 2mm thickness was cut to 60mm x 50mm, and the surface resistivity was measured in accordance with JIS K6911:1995 or ASTM D257. Specifically, the square plate prepared as described above was subjected to a surface resistivity measuring device, and the surface resistivity Rs (Ω) measured for 60 seconds at an applied voltage of 500V was multiplied by a surface resistivity correction coefficient specific to the device to evaluate the surface resistivity ρs (Ω / sq.). The surface resistivity ρs (Ω / sq.) is given by the following formula 1. (Formula 1): ρs=(V / I)×(W / L)=Rs×(W / L) V is the applied voltage, I is the current flowing on the surface of the test piece, W is the width of the electrode, and L is its length. This measurement was performed in accordance with ASTM D257. The inner diameter of the main electrode d was 25 mm, and the inner diameter of the outer ring electrode D was 750 mm. Therefore, the relationship between the surface resistance value Rs and the surface resistivity ρs was approximately calculated using the following formula 2. (Formula 2): ρs=30×Rs. Surface resistivity ρs (Ω / sq.) is 1.0×10 6 (Ω / sq.) or more, 1.0×10 16 (Ω / sq.), and more preferably less than 1.0×10 7 (Ω / sq.) or more, 1.0×10 15 (Ω / sq.), and more preferably less than 1.0×10 8 (Ω / sq.) or more, 1.0×10 12 (Ω / sq.) or less. In particular, the surface resistivity ρs (Ω / sq.) is less than 1.0×10 8 (Ω / sq.) or more, 1.0×10 10 (Ω / sq.), the thermoplastic polyester elastomer resin composition achieves both high reflection attenuation and transmission attenuation and exhibits good electromagnetic wave absorption properties.

[0094] [Electromagnetic wave absorption rate] A square plate measuring 80 mm x 80 mm x 2 mm was prepared as described in paragraph 0092. The direction of resin flow from the mold gate to the cavity is the MD direction, and the direction perpendicular to the resin flow direction is the TD direction. The electromagnetic wave absorption rate at a frequency of 76.5 GHz for the obtained square plate measuring 80 mm x 80 mm x 2 mm was calculated using the following formula (3). (Formula 3) TIFF2025060120000001.tif22166In the above formula (1), RL indicates the return loss measured by the free space method, and TL indicates the transmission loss measured by the free space method.To measure the electromagnetic wave absorption rate, we used a network analyzer N5252A manufactured by Keysight Technologies, which is an E-band free space method measuring device using millimeter waves.

[0095] The electromagnetic wave absorption rate (%) is preferably 60% or more, more preferably 65% ​​or more, and even more preferably 70% or more. The upper limit can be, for example, 90% or less, but is preferably 90% or more.

[0096] The thermoplastic polyester elastomer resin composition in this embodiment preferably has a high electromagnetic wave return loss (S11). The electromagnetic wave return loss at a frequency of 76.5 GHz for a square plate having dimensions of 80 mm×80 mm and a thickness of 2 mm can be calculated according to the following formula (4). (Formula 4) TIFF2025060120000002.tif22166 In the above formula (4), RL indicates the return loss measured by the free space method. In the case of the thermoplastic polyester elastomer resin composition in this embodiment, the return loss rate (S11) of the electromagnetic wave is 60% or more, preferably 65% ​​or more, and more preferably 70% or more. Although it is preferable that the upper limit of the return loss rate of the electromagnetic wave approaches 100%, since the thermoplastic resin composition does not theoretically reach 100%, the upper limit can be exemplified as 90%.

[0097] The thermoplastic polyester elastomer resin composition in this embodiment preferably has a high electromagnetic wave transmission attenuation rate (S21). The electromagnetic wave transmission attenuation rate at a frequency of 76.5 GHz in a square plate having dimensions of 80 mm x 80 mm and a thickness of 2 mm can be calculated according to the following formula (5). (Formula 5) TIFF2025060120000003.tif21166 In the above formula (3), TL indicates the transmission attenuation measured by the free space method. In the case of the thermoplastic polyester elastomer resin composition in this embodiment, the transmission attenuation rate of the electromagnetic wave (S21) is 80% or more, preferably 90% or more, and more preferably 95% or more. In the thermoplastic resin composition, the upper limit of the transmission attenuation rate of the electromagnetic wave is not theoretically 100%, but it is preferable that it approaches 100%, and an example of the upper limit is 99.9999% (-60 dB).

[0098] [Production of polyester block copolymer (A-1)] A polyester block copolymer (A-1) was produced, which had as its constituent components a hard segment (H) consisting of a crystalline aromatic polyester unit and a soft segment (L) consisting of an aliphatic polyether unit. 50.5 parts of terephthalic acid, 29.0 parts of 1,4-butanediol, and 35.4 parts of poly(tetramethylene oxide) glycol with a number average molecular weight of about 1400 were charged together with 0.04 parts of titanium tetrabutoxide and 0.02 parts of mono-n-butyl-monohydroxytin oxide in a reaction vessel equipped with a helical ribbon type stirring blade, and heated at 190 to 225 ° C for 3 hours, and an esterification reaction was carried out while discharging the reaction water out of the system. 0.2 parts of tetra-n-butyl titanate were added to the reaction mixture, and 0.05 parts of "Irganox" 1098 (a hindered phenol-based antioxidant manufactured by Ciba-Geigy) were added, and the temperature was raised to 245 ° C., and then the pressure in the system was reduced to 27 Pa over 50 minutes, and polymerization was carried out under those conditions for 1 hour and 50 minutes. The obtained polymer was discharged in the form of a strand into water and cut into pellets. The melting point of this thermoplastic polyester elastomer was 208°C.

[0099] [Production of polyester block copolymer (A-2)] A polyester block copolymer (A-2) was produced, the constituent components of which were a hard segment (H) consisting of a crystalline aromatic polyester unit and a soft segment (L) consisting of an aliphatic polyether unit, in which the hard segment (H) was composed of two types of acid components and a diol component. 33.0 parts of terephthalic acid, 10.0 parts of isophthalic acid, 40.3 parts of 1,4-butanediol, and 46.5 parts of poly(tetramethylene oxide) glycol with a number average molecular weight of about 1400, together with 0.04 parts of titanium tetrabutoxide and 0.02 parts of mono-n-butyl-monohydroxytin oxide, were charged into a reaction vessel equipped with a helical ribbon type stirring blade, and heated at 190 to 220 ° C for 3 hours, and an esterification reaction was carried out while discharging the reaction water out of the system. 0.15 parts of tetra-n-butyl titanate were added to the reaction mixture, and 0.05 parts of "Irganox" 1098 (a hindered phenol-based antioxidant manufactured by Ciba-Geigy) were added, and the temperature was raised to 245 ° C., and then the pressure in the system was reduced to 27 Pa over 50 minutes, and polymerization was carried out under those conditions for 1 hour and 50 minutes. The obtained polymer was discharged into water in the form of a strand, and cut into pellets. The melting point of this thermoplastic polyester elastomer was 162°C.

[0100] [First electromagnetic wave shielding material (B)] <Catalyst for carbon nanotube synthesis> 60 parts by mass of cobalt hydroxide, 138 parts by mass of magnesium acetate tetrahydrate, 16.2 parts by mass of manganese carbonate, and 4.0 parts by mass of Aerosil (AEOSIL (registered trademark) 200, manufactured by Nippon Aerosil Co., Ltd.) were weighed into a heat-resistant container, and dried in an electric oven at a temperature of 170 ± 5 ° C for 1 hour to evaporate moisture, and then ground for 1 minute using a grinder (Wonder Crusher WC-3, manufactured by Osaka Chemical Co., Ltd.). Then, the ground powders were mixed for 30 seconds using a grinder (Wonder Crusher WC-3, manufactured by Osaka Chemical Co., Ltd.) with the speed dial adjusted to 2 to prepare a catalyst precursor for carbon nanotube synthesis. The catalyst precursor for carbon nanotube synthesis was then transferred to a heat-resistant container and calcined for 30 minutes in an air atmosphere at 450 ± 5 ° C using a muffle furnace (FO510, manufactured by Yamato Scientific Co., Ltd.), and then ground in a mortar to obtain a catalyst for carbon nanotube synthesis. <Synthesis of carbon nanotubes> A quartz glass heat-resistant dish on which 2 g of the carbon nanotube synthesis catalyst was spread was placed in the center of a horizontal reaction tube with an internal volume of 10 L, which can be pressurized and heated by an external heater. The air in the reaction tube was replaced with nitrogen gas while nitrogen gas was injected, and the atmosphere in the horizontal reaction tube had an oxygen concentration of 1% by volume or less. The reaction tube was then heated by an external heater until the central temperature in the horizontal reaction tube reached 680°C. After reaching 680°C, propane gas was introduced into the reaction tube as a carbon source at a flow rate of 2L per minute and reacted for 1 hour. After the reaction was completed, the gas in the reaction tube was replaced with nitrogen gas, and the gas in the reaction tube was replaced with nitrogen gas, and the reaction tube was cooled to a temperature of 100°C or less and taken out to obtain carbon nanotubes, which are the first electromagnetic wave shielding material.

[0101] [Second electromagnetic shielding material (C)] As the second electromagnetic wave shielding material, carbon black "Niteron #10" (average primary particle size 39 nm) manufactured by Nippon Steel Carbon Corporation was used.

[0102] [Example 1] The polyester block copolymer obtained as described above was treated with carbon nanotubes, carbon black, and Hiwax NP056 (dispersant manufactured by Mitsui Chemicals) The mixture was dry-blended in the compounding ratio (parts by mass) shown in Table 1, and melt-kneaded using a twin-screw extruder having a triple-thread screw with a diameter of 45 mm, with a cylinder set temperature of 200°C for thermoplastic polyester elastomers with a melting point of 180°C or less, and a cylinder set temperature of 20°C higher than the melting point of the thermoplastic resin for thermoplastic polyester elastomers with a melting point of more than 200°C, and then discharged in the form of strands and pelletized with a pelletizer. The pellets were then measured for the physical properties of melting point, temperature showing the maximum value of the loss factor, surface hardness, tensile elongation at break, melt mass flow rate, Izod impact strength, surface resistivity, electromagnetic wave absorption rate, electromagnetic wave reflection attenuation rate, and electromagnetic wave transmission attenuation rate by the above-mentioned method. The measurement results are shown in Table 1 below.

[0103] [Example 2] Pellets of Example 2 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with the carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0104] [Example 3] Pellets of Example 3 were obtained in the same manner as in Example 1, except that the carbon black used in Example 1 was not used, and the carbon nanotubes and Hiwax NP056 were dry-blended with the polyester block copolymer in the compounding ratio (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0105] [Example 4] Pellets of Example 4 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with the carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0106] [Example 5] Pellets of Example 5 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with the carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0107] [Example 6] Pellets of Example 6 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with the carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0108] [Example 7] Pellets of Example 7 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with the carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0109] [Example 8] Pellets of Example 8 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 1 below.

[0110] [Comparative Example 1] Pellets of Comparative Example 1 were obtained in the same manner as in Example 1, except that the carbon nanotubes used in Example 1 were not used, and carbon black and Hiwax NP056 were dry-blended with the polyester block copolymer in the compounding ratio (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 2 below.

[0111] [Comparative Example 2] Pellets of Comparative Example 2 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 2 below.

[0112] [Comparative Example 3] Pellets of Comparative Example 3 were obtained in the same manner as in Example 1, except that the polyester block copolymer was dry-blended with carbon nanotubes, carbon black, and Hi-Wax NP056 in the blending ratios (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 2 below.

[0113] [Comparative Example 4] Pellets of Comparative Example 4 were obtained in the same manner as in Example 1, except that a polybutylene terephthalate resin "TORECON" 1100S (A'-3) manufactured by Toray Industries, Inc. was used instead of the polyester block copolymer, and carbon nanotubes, carbon black, and Hiwax NP056 were dry-blended with the polybutylene terephthalate resin in the compounding ratio (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 2 below.

[0114] [Comparative Example 5] Pellets of Comparative Example 5 were obtained in the same manner as in Example 1, except that a polyamide resin "Amilan" CM1017 (A'-4) manufactured by Toray Industries, Inc. was used instead of the polyester block copolymer, and carbon nanotubes, carbon black, and Hi-Wax NP056 were dry-blended with the polyamide resin in the compounding ratio (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 2 below.

[0115] [Comparative Example 6] Pellets of Comparative Example 6 were obtained in the same manner as in Example 1, except that a polypropylene resin "Prime Polypro J707G" (A'-5) manufactured by Prime Polymer Co., Ltd. was used instead of the polyester block copolymer, and carbon nanotubes, carbon black, and Hi-Wax NP056 were dry-blended with the polypropylene resin in the blending ratio (parts by mass) shown in Table 1, and the physical properties were measured. The measurement results are shown in Table 2 below.

[0116] [Table 1]

[0117] [Table 2]

[0118] As shown in Table 1, a thermoplastic polyester elastomer resin (A), a first electromagnetic wave shielding material (B), and a second electromagnetic wave shielding material (C) are blended within the range of the present invention. The molded bodies of Examples 1 to 8 have high toughness, impact resistance, excellent molding processability, high electromagnetic wave reflection attenuation rate, high electromagnetic wave transmission attenuation rate, appropriate surface resistivity, and appropriate electromagnetic wave absorption rate, and are therefore excellent electromagnetic wave shielding materials.

[0119] However, since the molded body of Comparative Example 1 does not contain carbon nanotubes as the first electromagnetic wave shielding material (B), it has low electromagnetic wave transmission attenuation rate and electromagnetic wave absorption rate, and is therefore not suitable as an electromagnetic wave shielding material. In addition, since the molded body of Comparative Example 2 has a small total blend amount of the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C), it has a low electromagnetic wave transmission attenuation rate and electromagnetic wave absorption rate, and is therefore not suitable as an electromagnetic wave shielding material. In addition, since the molded body of Comparative Example 3 has a large total blend amount of the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C), it has low tensile break elongation and poor mechanical properties, a low melt mass flow rate and poor melt processability, and a low electromagnetic wave reflection attenuation rate and electromagnetic wave absorption rate, and is therefore not suitable as an electromagnetic wave shielding material. In addition, since the molded article of Comparative Example 4 does not use the thermoplastic polyester elastomer resin of the present invention, it has low tensile break elongation and poor mechanical properties, a high temperature at which the loss factor tan δ shows a maximum value and a low Izod impact strength, resulting in poor impact resistance, and low electromagnetic wave transmission attenuation and electromagnetic wave absorption rates, and is therefore not suitable as an electromagnetic wave shielding material. Furthermore, since the molded article of Comparative Example 5 does not use the thermoplastic polyester elastomer resin of the present invention, it has low tensile elongation at break and poor mechanical properties, and the temperature at which the loss factor tan δ shows a maximum value is high and the Izod impact strength at low temperature (-20°C) is low, resulting in poor impact resistance, and it is therefore not suitable as an electromagnetic wave shielding material. Furthermore, since the molded body of Comparative Example 6 does not use the thermoplastic polyester elastomer resin of the present invention, it has low tensile breaking elongation and therefore poor mechanical properties, and also has low Izod impact strength and therefore poor impact resistance, and is therefore not suitable as an electromagnetic wave shielding material. [Industrial Applicability]

[0120] The thermoplastic polyester elastomer resin composition of the present invention is useful as a molding material having high flexibility and impact resistance in low to high temperature ranges, excellent melt processability and moldability, and high electromagnetic wave absorption properties, mainly millimeter waves, compared with conventional general-purpose engineering plastic compositions. For example, it is expected to be applied to in-vehicle millimeter wave radars, railway and aviation millimeter wave radars, millimeter wave radars for traffic infrastructure, millimeter wave radars for various security devices, medical and nursing care millimeter wave radars, and millimeter wave radars for network transmission.

Claims

1. A thermoplastic polyester elastomer resin composition comprising 80.0 to 99.5 mass% of a thermoplastic polyester elastomer resin (A) and 0.5 to 20.0 mass% in total of a first electromagnetic wave shielding material (B) and a second electromagnetic wave shielding material (C), wherein the first electromagnetic wave shielding material (B) is contained in the thermoplastic polyester elastomer resin (A) in an amount such that the reflection attenuation rate of electromagnetic waves is 60% or more, and the second electromagnetic wave shielding material (C) is contained in the thermoplastic polyester elastomer resin (A) in an amount such that the transmission attenuation rate of electromagnetic waves is 80% or more, and wherein the thermoplastic polyester elastomer resin (A) is a polyester block copolymer mainly composed of 80 to 10 mass% of a high melting point crystalline polymer segment (a1) mainly composed of a crystalline aromatic polyester unit and 10 to 80 mass% of a low melting point polymer segment (a2) mainly composed of an aliphatic polyether unit and / or an aliphatic polyester unit.

2. The thermoplastic polyester elastomer resin composition according to claim 1, wherein when a 2 mm thick plate obtained by molding the thermoplastic polyester elastomer resin composition is irradiated with electromagnetic waves having a frequency of 76 GHz to 80 GHz, the electromagnetic wave absorption rate measured by a free space method is 60% to 90%.

3. The thermoplastic polyester elastomer resin composition according to claim 1, wherein the temperature at which the loss factor shows a maximum value as measured by a tensile vibration non-resonance method in accordance with JIS K7244 is 20°C or lower.

4. 2. The thermoplastic polyester elastomer resin composition according to claim 1, wherein a test piece molded in accordance with JIS K7161 has a tensile elongation at break of 200% or more.

5. The thermoplastic elastomer resin composition according to claim 1, having a notched Izod impact strength of 200 J / m notch or more measured at a temperature of 23°C and a notched Izod impact strength of 100 J / m notch or more measured at a temperature of -20°C according to JIS K7110.

6. The thermoplastic polyester elastomer resin composition according to claim 1, wherein the first electromagnetic wave shielding material (B) is carbon nanotubes and the second electromagnetic wave shielding material (C) is carbon black.

7. The surface resistivity of a molded product obtained by molding the thermoplastic polyester elastomer resin composition is 1.0×10 6 (Ω / sq.) or more 1.0×10 16 The thermoplastic polyester elastomer resin composition according to claim 1, wherein the elastic modulus is less than (Ω / sq.).

8. The thermoplastic polyester elastomer resin composition according to claim 1, further comprising a dispersant (D) for dispersing the first electromagnetic wave shielding material (B) and the second electromagnetic wave shielding material (C) in the thermoplastic polyester elastomer resin.

9. The thermoplastic polyester elastomer resin composition according to claim 8, wherein the dispersant is any one of paraffin wax, montan wax, amide wax, ethylene bisstearic acid amide, fatty acid metal salt, silicone, and polyolefin wax, or any combination thereof.

10. 10. An electromagnetic wave shielding material obtained by molding the thermoplastic polyester elastomer resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition for electromagnetic wave absorber and electromagnetic wave absorber

    JP2023067902A

  • Electromagnetic wave absorber and method for manufacturing the same

    JP6905834B2

  • Thermoplastic resin composition for electromagnetic wave absorber and molded article

    JP6927448B1

Cited By

  • Wave-absorbing material with impedance gradient core-shell structure as well as preparation method and application of wave-absorbing material

    CN122436717A